History and Historiography of Coerced Sterilizations of Romani Women in Czechoslovakia and Their Continuing Resonances. Introduction to the Special Issue of Romano džaniben - Sadílková, Helena (Romano džaniben, 2019)
The text summarizes the history and mechanisms of sterilisation policies in communist Czechoslovakia targetting Romani women and the history of the fight for its critical acknowledgement, condemnation and compensation. It also outlines the history of the documentation of this practice and the attempts of its inclusion in history writing. Highlighting the results of the existing reseach the author notes the impossiblity of a simple inclusion of the topic into the debate on the "crimes of the communist regime" as the genesis of this practice and history of its implementation points to important social prerequisits and continuities. The text commnets on the blind spots of the existing research, including especially the reaction of the Roma as social actors of the time. It also points to another important topic: the genesis of experience of Czechoslovak post-war authorities with the design and negotiation of policies outside constitutional limits aimed at targetting the Roma.